A temporal switch in the insulin-signalling pathway that regulates hepatic IGF-binding protein-1 gene expression - Finlay, David (My University, 2006)
Insulin regulation of hepatic gene transcription is a vital component of glucose homeostasis. Understanding the molecular regulationof thisprocess aids the searchfor the defect(s) that promotesinsulin-resistant states, such asdiabetesmellitus. We havepreviously shownthat the insulin regulationof hepatic IGF-binding protein-1 (IGFBP1) expression requiresthe signalling proteins phosphatidylinositol 3-kinase (PI 3-kinase) and mammalian target of rapamycin (mTOR). In this report, we demonstrate that activation of the mTOR pathway, without activation of its upstream regulator PI 3-kinase, reduces IGFBP1 expression. Therefore, mTOR activation is sufficient to mimic insulin regulation of this gene. However, longer exposure (>3 h) of cells to insulin reduces the importance of this pathway in insulin regulation of the gene, suggesting a temporal switch in signalling mechanisms linking insulin action to the IGFBP1 gene promoter. In contrast, the activation of PI 3-kinase is required for insulin regulation of IGFBP1 under all conditions tested. Therefore, an mTOR-independent, PI 3-kinase-dependent pathway becomes more important in IGFBP1 regulation after long exposure to insulin. This is a novel concept in insulin regulation of gene expression and demonstrates the importance of temporal analysis of signalling processes.
PUBLISHED
Keywords: Genetics; Insulin